KETERLAKSANAAN KURIKULUM 2013 MATA PELAJARAN PENJASORKES DI SEKOLAH DASAR SE-KECAMATAN MELIAU - Widia Tri Eksanurianto; Eka Supriatna; Fitriana Puspa Hidasari (STKIP Melawi, 2021)
Abstract: Public Elementary Schools in Meliau District have not been able to implement the 2013 curriculum, due to incomplete supporting facilities to implement the 2013 curriculum. The aim of this research is to achieve know the implementation of the 2013 curriculum for Physical Education subjects in Elementary Schools in Meliau District. This research is a quantitative research with descriptive research type, with survey methods and data collection techniques using a questionnaire. The subjects in this study were 28 teachers of PJOK SD in Meliau District. To analyze the data used descriptive statistics with percentages. Based on the results of the study, it is known that the implementation of the 2013 curriculum for physical education and health services in elementary schools throughout Meliau District in implementing the 2013 curriculum is in the very high category of 0%, the high category is 7.1%, the moderate category is 67.9%, the low category is 21.4 % and very low category of 3.6%. Based on these results it can be concluded that the implementation of the 2013 curriculum for Physical Education subjects in Elementary Schools in Meliau District is mostly in the medium category.Keywords: Elementary schools, implementation of PJOK teachers, Implementation of the 2013 curriculumAbstrak: Sekolah Dasar Negeri di Kabupaten Meliau belum mampu melaksanakan kurikulum 2013, dikarenakan fasilitas pendukung yang belum lengkap untuk melaksanakan kurikulum 2013. Tujuan dari penelitian ini adalah untuk mengetahui implementasi kurikulum 2013 mata pelajaran Pendidikan Jasmani di Sekolah Dasar di Kabupaten Meliau. Penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian deskriptif, dengan metode survei dan teknik pengumpulan data menggunakan kuesioner. Subjek dalam penelitian ini adalah 28 guru SD PJOK di Kabupaten Meliau. Untuk menganalisis data digunakan statistik deskriptif dengan persentase. Berdasarkan hasil penelitian diketahui bahwa implementasi Kurikulum 2013 Pendidikan Jasmani dan Pelayanan Kesehatan di Sekolah Dasar se-Kabupaten Meliau dalam melaksanakan Kurikulum 2013 berada pada kategori sangat tinggi yaitu 0% kategori tinggi 7,1. %, kategori sedang 67.9%, kategori rendah 21.4% dan kategori sangat rendah 3.6%. Berdasarkan hasil tersebut dapat disimpulkan bahwa implementasi kurikulum 2013 mata pelajaran Pendidikan Jasmani di Sekolah Dasar di Kabupaten Meliau sebagian besar berada pada kategori sedang.Kata Kunci: Sekolah Dasar, Penerapan Guru PJOK, Penerapan Kurikulum 2013